Measuring protein stability in the GroEL chaperonin cage reveals massive destabilization - Korobko, Ilia; Mazal, Hisham; Haran, Gilad; Horovitz, Amnon (eLife, 2020)
The thermodynamics of protein folding in bulk solution have been thoroughly investigated for decades. By contrast, measurements of protein substrate stability inside the GroEL/ES chaperonin cage have not been reported. Such measurements require stable encapsulation, that is no escape of the substrate into bulk solution during experiments, and a way to perturb protein stability without affecting the chaperonin system itself. Here, by establishing such conditions, we show that protein stability in the chaperonin cage is reduced dramatically by more than 5 kcal mol−1 compared to that in bulk solution. Given that steric confinement alone is stabilizing, our results indicate that hydrophobic and/or electrostatic effects in the cavity are strongly destabilizing. Our findings are consistent with the iterative annealing mechanism of action proposed for the chaperonin GroEL.
Keywords: chaperones; protein folding; protein stability